2006
DOI: 10.1111/j.1439-037x.2006.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Yield–Density Relation of Glyphosate‐Resistant Soya beans and their Responses to Light Enrichment in North‐eastern USA

Abstract: Optimum plant population densities are a key means of achieving higher seed yield in soya bean [Glycine max (L.) Merr.]. Limited information is available on yield-density relation of glyphosate-resistant soya beans in north-eastern USA. The objective of this research was to determine the appropriate populations for glyphosate-resistant soya beans, and if the yield potential of glyphosate-resistant soya bean produced in light-enriched conditions was affected by populations. Eight glyphosate-resistant soya bean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…The environments, therefore, affect the pod productivity and then affect the seed yield per plant for the soybean accessions tested. Further more, the yield variation is not only influenced by external factors which mostly determined by different environmental conditions but also it also is influenced by internal factors especially the genetic make-up of the soybean accessions (Liu et al, 2006) as clearly demonstrated by this study. …”
Section: Yield and Yield Components Performances Of 56 Soybean Acessisupporting
confidence: 55%
“…The environments, therefore, affect the pod productivity and then affect the seed yield per plant for the soybean accessions tested. Further more, the yield variation is not only influenced by external factors which mostly determined by different environmental conditions but also it also is influenced by internal factors especially the genetic make-up of the soybean accessions (Liu et al, 2006) as clearly demonstrated by this study. …”
Section: Yield and Yield Components Performances Of 56 Soybean Acessisupporting
confidence: 55%
“…That is either to increase pod number per plant or seed number per pod. Liu et al (2006b) suggested that some internal factors rather than external input regulate the seed number per pod in some cultivars. The variation in seed number per pod observed at the extreme node positions was much greater than that at the middle mainstem nodes of soybean plants.…”
Section: Resultsmentioning
confidence: 99%
“…High populations provide a way to optimize grain yields in shortseason production systems (Liu et al 2006b). The breeding and selection of semi-dwarf cultivars and adoption of narrow row spacing made high densities possible, and thus increased soybean yield (Svecnjak et al 2006).…”
mentioning
confidence: 99%
“…Liu et al (2006) and Liu et al, 2008) reported that application of appropriate plant density help reducing the time required for canopy closure, improving crop growth and consequently biomass and grain yield of soybean production systems. Although most of the soils used to cultivate soybean in Benin are degraded, producers in their majority do not use fertilizers to improve soil fertility level and they still claim that soybean does not need fertilizers for growth.…”
Section: Cropping Practices and Determinants Of Soybean Yield Level Imentioning
confidence: 99%